Evolution of the mechanical properties of a medical device regarding implantation time. (November 2019) - G.Doucède,; Morch, A.; Pouseele, B.; Lecomte-Grosbras, P.; Brieu, M.; Cosson, M.; Rubod, C.
Abstract: Background: Our study aimed at understanding the influence of healing time on the mechanical properties of meshes used in pelvic organ prolapse, once implanted in an animal model using the rat. Methods: A standard polypropylene mesh was implanted in 42 rats in order to evaluate the mechanical properties of the implanted mesh. Explantation occurred at 1, 2, 3, 4 and 5 months and mechanical tests were performed. Each sample was mechanically evaluated by a uniaxial tensile test with a machine (BIOTENS). Biological tissues presented a nonlinear relation between stress and strain so it could be modeled by the 2 parameters C0 and C1 of a second-order Mooney-Rivlin law. Results: The rigidity in small deformation might not be affected by healing time or the presence of the synthetic implant. On the contrary, changes seemed to occur on the stiffness in large deformation (C1 ). The stiffness with the mesh composite changed with healing time. The "two-month implantation" rat group was significantly more rigid than the two control groups (pcontrol/2months = 0, 04 and pplacebo/2months = 0, 04). The 2- and 3-month healing groups were significantly more rigid than the 1-month healing group (p 1/2months = 0, 01 and p 1/3months = 0, 003). After 2 months, the mechanical properties seemed to stabilize (p 2/3months = 0, 44, p 2/5months = 0, 16 et p 3/5months = 0, 3). Conclusion: In order to evaluate the mechanical properties of an implanted mesh, the optimal time for explantation seems to be 2 months. Once this period is over, a more physiological mesh will be developed in order to be similar to native vaginal tissue once implanted and colonized by scar tissue.